Plasma and Urine Biomarkers in Chronic Kidney Disease - Khader Samin, Nabil Ibrahim; Mohammed Ahmed, Aseel Abdulazeez; Faraj, Saja Ali Muhaibis; Ismael, Lubna Hamed Yassin; majeed abd, Mustafa Yaseen (American Journal of Biomedicine and Pharmacy, 2025)
General Background: Chronic kidney disease (CKD) is a progressive condition affecting a significant proportion of the global population, characterized by impaired renal function and associated with high morbidity and mortality. Specific Background: The disease often remains undiagnosed in its early stages due to the absence of noticeable symptoms, leading to late-stage diagnosis and limited treatment options. Biomarkers such as urea, creatinine, albumin, total protein, and glucose are commonly used to assess kidney function, yet their diagnostic utility requires further validation. Knowledge Gap: Despite the clinical importance of these biomarkers, there remains insufficient evidence regarding their early diagnostic value and their comparative significance in CKD progression. Aims: This study aims to evaluate the levels of key plasma and urine biomarkers in CKD patients compared to a control group, providing insights into their potential role in early detection. Results: The findings reveal significantly elevated levels of urea, creatinine, and glucose in CKD patients, while albumin and total protein levels were markedly reduced. Statistical analysis confirmed the significance of these differences, reinforcing their association with CKD pathology. Novelty: This study provides empirical validation of biomarker alterations in CKD, offering a comprehensive comparison of their diagnostic relevance. Implications: The results emphasize the need for improved screening strategies utilizing these biomarkers for earlier detection, facilitating timely intervention and reducing disease progression risks. These insights contribute to refining CKD diagnostic approaches and optimizing patient management strategies.